2020
DOI: 10.1002/pssa.202000221
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy and Mechanistic Elucidation of Wet‐Chemical Gallium Nitride Etching at the Atomic Level

Abstract: Etching of gallium nitride is a key step in the production of blue and white light‐emitting diodes (LEDs). Etching in aqueous KOH solution creates a rough surface on the LED chip to facilitate outcoupling of the photons generated, drastically increasing the resulting LED's efficiency. Compared with the common technique of dry etching, wet‐chemical etching using aqueous KOH solution has significant advantages, e.g., lower complexity and cost and less remaining surface damage. An in‐depth analysis of the molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
(57 reference statements)
0
23
1
Order By: Relevance
“…This has led to an opportunity for hydroxide ions to reach Ga atoms in defect-rich areas progressing the wet etching process. 42,43 More detailed explanation and characteristics of this hybrid etching method combining both ICP-RIE and KOHbased wet etching processes on different stacks of GaN layers have been described in our former studies and the reports from other groups. 42−46 We have also demonstrated to employ this hybrid etching technique for realizing both field-effect transistors and LEDs based on vertical GaN nanowire arrays.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…This has led to an opportunity for hydroxide ions to reach Ga atoms in defect-rich areas progressing the wet etching process. 42,43 More detailed explanation and characteristics of this hybrid etching method combining both ICP-RIE and KOHbased wet etching processes on different stacks of GaN layers have been described in our former studies and the reports from other groups. 42−46 We have also demonstrated to employ this hybrid etching technique for realizing both field-effect transistors and LEDs based on vertical GaN nanowire arrays.…”
Section: Methodsmentioning
confidence: 97%
“…Afterward, the sample was subsequently treated in a potassium hydroxide (KOH)-based wet chemical etchant to smoothen the GaN surface at a temperature of 80 °C for 20 min. From other reported studies using hydroxide ions (OH – ) as an active etchant, it was found that Ga- and N-polar GaN materials possess different etching behaviors. As a key prerequisite for anisotropic KOH etching to occur on GaN, the hydroxide ions have to be able to access the Ga atom for the oxidation process. Thus, hexagonal pyramids can be formed when N-polar GaN areas were exposed to KOH solution .…”
Section: Methodsmentioning
confidence: 99%
“…where I x and I sub are the peak intensities of the species and substrate, respectively, l sub is the effective attenuation length for quantitative analysis (NIST database), and N sub is the atomic concentration (Ga + N) in the substrate (at cm −3 ). 36 22,[26][27][28]32 A typical etch rate for a 1 M KOH solution at 80 °C is 25 nm/min. 33 The dissolution reaction is described using eq 1 22, 30,31 GaN 3H O OH Ga(OH) NH…”
Section: Methodsmentioning
confidence: 99%
“…26,29−32 It is surprising that relatively little attention has been paid to the basic chemistry involved in the uniform etching process. 23,30,32 This will be the main topic in the first part of the paper (Section 3.1). In a previous study by Weyher et al 33 it was shown that, after brief photogalvanic etching, subsequent chemical etching of the Ga-polar surface was possible.…”
Section: Introductionmentioning
confidence: 99%
“…Figure12. The surface was covered (for simplicity) with a 300 nm-thick carbon layer, which was patterned by FIB (dark spots in the image).…”
mentioning
confidence: 99%